STRUCTURE AND MECHANICAL PROPERTIES OF POLYMERIC COMPOSITES WITH CARBON NANOTUBES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Experimental investigations of single-wall carbon nanotubes (CNT) effect on the mechanical properties of polymeric composite materials based on epoxy matrix have been carried out. It has been found that addition of CNT at low concentration dramatically increases tensile strength (20 – 30 per cent growth) and Young’s modulus of the samples under study. Structure of polymeric composites with CNT was characterized by atomic force microscopy (AFM) and scanning electron microscopy (SEM). AFM images of the samples under study confirm strong interaction between polymeric matrix and nano-additives, demonstrating intimate contact between CNT and epoxy surroundings which is of great importance for composite material reinforcement. Dependences of tensile strength and those of Young’s modulus on CNT concentration are discussed using micromechanics models for nanocomposites.